Diretor em ação: entre a burocracia e o cotidiano da escola - Silva, Tathyana Gouvêa da (2010)
This dissertation aims to identify, to describe and to understand the actions of the school principals. To do such, the actions of four principals who have worked in a public middle school of the state net located in São Paulo were followed during one year (from September of 2008 until August of 2009). It was intended to notice which are the actions of the school principal, what motivates those actions and what are its implications. This analysis is supported on the Weber´s theory about social action and bureaucracy and in the concepts of action and practice of Gimeno Sacristan. For the comprehension of the action it was sought to identify the legal attributes of the position and characterizes the school organization and the investigated people. It was done through historic-legal survey, observations, not structured interviews and the application of an inquiry form with the four principals. The analysis of the actions based on the analytic model of Gimeno Sacristan supplied evidences that the principals perform seven kinds of actions educational and professional assistance, social environment, coordination, control, information sharing, management and representation, which arises from the rules which comes with bureaucracy and of the current situations brought up by the school´s singularity. The actions of the school principal are showed directly on the school organization, in its social structure, lay-out and management, at the same time being the base of the experience of the human-beings who perform it and the source of change or maintenance of the structures which compose the culture